Nasolaryngeal Distances in the Adult Population and an Evaluation of Commercially Available Nasotracheal Tubes. (April 2020) - Massoth, Christina; Schülke, Christoph; Köppe, Jeanette; Weiss, Raphael; Pöpping, Daniel; Dahrmann, Michael; Zarbock, Alexander; Wenk, Manuel
Abstract : BACKGROUND: Preformed nasal endotracheal tubes (NETs) come with a predefined insertion depth due to their curved design. While size indication refers to internal diameter, there is a considerable variability in the corresponding lengths and proportions of same-sized tubes of different manufacturers which is probably based on the lack of data of nasolaryngeal distances (NLDs) in the adult population. Choosing the best-fitting NET is therefore difficult and carries the risk of endobronchial intubation or, on the contrary, cuff inflation at the vocal cord level. The aim of this study was to develop a prediction model for NLD and a selection guide to choose the appropriate NET based on a radiographic description of NLD in comparison to the measurements of available NETs of several manufacturers. METHODS: After institutional ethics board review, 388 computed tomography (CT) scan images of head, neck, and upper thorax in a heterogeneous adult cohort were included. Mean distances from the nares to the lower border of the thyroid cartilage were measured. NETs from different manufacturers were measured and compared to the NLD derived from the radiographic analysis. The patients' sex, body height, and weight were considered as possible covariates in quantile regression models for predicting the NLD. RESULTS: Data from 200 patients were analyzed. NLD was associated with sex, body height, and weight. A simple quantile regression model using the body height as the only covariate sufficed to achieve accurate predictions of NLD. Validation on independent test data showed that 92.8% of the NLD predictions were closer than ±20 mm to the observed NLD values. Measurements of equal-sized NETs varied considerably in outer diameter, proportion, the nasopharyngeal part, and guide marks. Length differences of the bend-to-cuff distance, containing the anatomically NLD, ranged between 218 and 270 mm at same sizes. CONCLUSIONS: A reliable prediction of NLD can be obtained simply by body height, using the formula . As manufacturers' tube lengths vary substantially, additional information about the bend-to-cuff distance as corresponding tube section would allow for more accurate tube selection.